Perspectiva veterinaria del sistema renal en la sepsis - Gasser, Beatriz [UNESP]; Ramirez-Uscategui, Ricardo A.; Maronezi, Marjury [UNESP]; Rodrigues-Simões, Ana [UNESP]; Pérez-Gomes, Luiz [UNESP]; Pavan, Letícia [UNESP]; Rossi-Feliciano, Marcus [UNESP] (Universidad de Cordoba, 2021)
This paper aims to review, discuss and define the factors associated with development of kidney injury in patients with sepsis, diagnosis alternatives, therapy and prevention, offering to the veterinarians an updated guide to improve the prognosis of sepsis patients. Sepsis is a clinical condition that leads to systemic complications and to multiple organ dysfunction syndrome (MODS), mainly due to poor tissue perfusion in humans and animals. Acute kidney injury (AKI) is considered the most frequent and lethal among organ complications secondary to sepsis, however the etiology of AKI in patients with sepsis is complex and multifactorial and not completely elucidated. Early diagnosis of AKI is difficult and consequently the treatment is not very successful, due to hemodynamic aspects. The ultrasonography seems to be a promising exam for early diagnosis of this lesion, especially with the advent of contrast-enhanced ultrasonography (CEUS) technique, which makes possible to detect microcirculation changes in the renal parenchyma, opening the door for a variety of physiological, clinical and therapeutic applications, however, studies proving CEUS accuracy for early detection of renal damage related to sepsis in humans and animals are still necessary.
Keywords: Acute kidney injury; infection; inflammation; multiple organ failure; perfusion; renal blood flow (Source: DeCS)